1957
DOI: 10.1172/jci103514
|View full text |Cite
|
Sign up to set email alerts
|

Study of Urinary and Fecal Excretion of Radioactive Chromium Cr51 in Man. Its Use in the Measurement of Intestinal Blood Loss Associated with Hookworm Infection1

Abstract: Since the work of Cruz (1) and Rhoads, Castle, Payne, and Lawson (2) iron deficiency has been attributed a pre-eminent role in the causation of the anemia associated with hookworm infection. At one time or another, however, this anemia has been blamed on the effect of hemolytic "toxins" from the hookworm, poor iron absorption, poor protein intake, and blood loss, or a combination of all or several of these factors. An exact evaluation of the role of each of these possible causes is not feasible until quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

1960
1960
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(22 citation statements)
references
References 10 publications
4
17
0
1
Order By: Relevance
“…The recovery of 97.4% of relatively small orally administered doses of 51Cr-labelled red cells suggests that apparently hardly any of the 51Cr is absorbed from the gut, and thus agrees with the results of Owen et al (1954), Roche et al (1957), andEbaugh et al (1958). Hughes Jones (1958) gave oral doses of 21,uC of 51Cr and 8 tC to two patients, and was only able to recover 66% and 87% of the administered dose.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The recovery of 97.4% of relatively small orally administered doses of 51Cr-labelled red cells suggests that apparently hardly any of the 51Cr is absorbed from the gut, and thus agrees with the results of Owen et al (1954), Roche et al (1957), andEbaugh et al (1958). Hughes Jones (1958) gave oral doses of 21,uC of 51Cr and 8 tC to two patients, and was only able to recover 66% and 87% of the administered dose.…”
Section: Resultssupporting
confidence: 89%
“…of whole blood was found. A similar figure was obtained by Hughes Jones (1958), and Levin, Hart, and Bothwell (1959) but is rather less than the quantity found by Roche et al (1957) and Ebaugh et al (1958), namely 1.2 ml. It has been suggested that this difference may be due to the fact that these authors did not remove the unattached 51Cr by washing their cells after labelling (Hughes Jones, 1958).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The upper limit of normal intestinal blood loss as determined by radioisotope studies have been reported to range from 1 to 3 ml/day. 5,11,12 The stool samples were moistened with drops of distilled water immediately prior to occult blood testing since rehydration has been shown to improve the sensitivity of the guaiac test. 13 The observer developing and reading the Coloscreen slide was blinded to the parasitologic result.…”
Section: Methodsmentioning
confidence: 99%